2016
DOI: 10.1177/1535370215627033
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide protects against cognitive impairment induced by hepatic ischemia and reperfusion via attenuating neuroinflammation

Abstract: Previously, hepatic ischemia followed by reperfusion (hepatic I/R) has been found to cause cognitive impairment. Hydrogen sulfide (H 2 S) attenuates hepatectomy induced cognitive deficits and also protects against cognitive dysfunction induced by neurodegenerative diseases. In this study, we aim to determine whether sodium hydrosulfide (NaHS), a H 2 S donor, could alleviate hepatic I/R-induced cognitive impairment and the underlying mechanisms. Rats were injected intraperitoneally with NaHS (5 mg/kg/d) for 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Compared with the control group, ROS levels were not significantly increased in rats treated with NaHS alone (Figures 3 and 2) and Nrf2 nuclear translocation or the increase in SOD, HO-1, and NQO-1 expression was not observed (Figures 2 and 5). These findings above are consistent with previous studies [34,35,38,39]. SIRT3 is a histone deacetylase localized predominantly in mitochondria and regulates mitochondrial enzymatic…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Compared with the control group, ROS levels were not significantly increased in rats treated with NaHS alone (Figures 3 and 2) and Nrf2 nuclear translocation or the increase in SOD, HO-1, and NQO-1 expression was not observed (Figures 2 and 5). These findings above are consistent with previous studies [34,35,38,39]. SIRT3 is a histone deacetylase localized predominantly in mitochondria and regulates mitochondrial enzymatic…”
supporting
confidence: 93%
“…PQ was intraperitoneally administered in rats at a dose of 20 mg/kg which was based on our previous study [10]. With reference to the previous studies [33][34][35], two different doses of NaHS as mentioned above were administered intraperitoneally one hour prior to exposure to PQ. At 12 h, 24 h, and 48 h after PQ administration, the rats (n = 6) were taken from each group and sacrificed after deep anesthesia at each time point.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…There is evidence that NaHS, which releases H 2 S when in aqueous solution, is protective in a variety of animal models of disease . Tu et al have demonstrated that NaHS (5 mg/kg/day for 11 days, ip) protects against cognitive impairment induced by hepatic ischemia‐reperfusion via attenuating neuroinflammation . Du et al have demonstrated that NaHS (0.78, 1.56, and 3.12 mg/kg, ip) is positively correlated with the dosage provided a protective effect against acute lung injury in the LPS‐induced rat models .…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S, a gaseous signaling molecule, scavenges ROS and protects neurons against oxygen stress damage, neurotoxicity, and cell apoptosis [ 33 , 34 ]. Furthermore, H 2 S plays an important role in regulation of learning and memory [ 10 ]. To investigate the beneficial effect of H 2 S on CRS-induced deficits in learning and memory, rats were cotreated with NaHS and CRS for 28 d, and the functions of learning and memory of rats were tested with Y-maze test, Novel object recognition test, and Morris water maze test.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen sulfide (H 2 S), the third gasotransmitter along with nitric oxide (NO) and carbon monoxide (CO) [ 5 ], plays potent protective effects in the central nervous system [ 6 , 7 ]. Accumulating evidences demonstrate that H 2 S facilitates the induction of hippocampal long term potentiation (LTP) [ 8 , 9 ] and attenuates hepatic I/R- or β-amyloid-induced impairment in spatial learning and memory [ 10 - 13 ]. Moreover, our recent study certified that disturbance of endogenous H 2 S generation in hippocampus is involved in deficits in learning and memory [ 14 , 15 ] and that H 2 S antagonizes formalydehyde-exerted deficits in cognitive function [ 16 ].…”
Section: Introductionmentioning
confidence: 99%